Answer:
Step-by-step explanation:
PART 1:
Possible roots by noticing the coefficient of first term:
x = 1, -1
PART 2:
1 | 1 -1 -4 4
<u> 1 0 -4</u>
1 0 -4 0
The remainder is zero, hence one factor is (x-1)
PART 3:
![x^3-x^2-4x+4=(x^2-4)(x-1)\\\\x^3-x^2-4x+4=(x+2)(x-2)(x-1)](https://tex.z-dn.net/?f=x%5E3-x%5E2-4x%2B4%3D%28x%5E2-4%29%28x-1%29%5C%5C%5C%5Cx%5E3-x%5E2-4x%2B4%3D%28x%2B2%29%28x-2%29%28x-1%29)
PART 4:
![f(x)=(x+2)(x-2)(x-1)\\\\=(x^2-4)(x-1)\\\\=x^3-4x-x^2+4\\\\=x^3-x^2-4x+4](https://tex.z-dn.net/?f=f%28x%29%3D%28x%2B2%29%28x-2%29%28x-1%29%5C%5C%5C%5C%3D%28x%5E2-4%29%28x-1%29%5C%5C%5C%5C%3Dx%5E3-4x-x%5E2%2B4%5C%5C%5C%5C%3Dx%5E3-x%5E2-4x%2B4)
Answer: 1:3
Step-by-step explanation: You would divide both sides by 6 and get 1:3 poodles to beagles
Hey there! I'm happy to help!
If you raise a fraction to an exponent, you apply that exponent to the numerator and the denominator. This would give us
.
Have a wonderful day! :D
Answer:
third in line
Step-by-step explanation:
hope this helps